2020
DOI: 10.3390/antiox9060548
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidative Effects of Thymus quinquecostatus CELAK through Mitochondrial Biogenesis Improvement in RAW 264.7 Macrophages

Abstract: Oxidative stress plays a key role in the pathogenesis of several diseases, including neurodegenerative diseases. Recent studies have reported that mitochondrial dysfunction is a leading cause of the overproduction of reactive oxygen species and oxidative stress. Mitochondrial changes play an important role in preventing oxidative stress. However, there is a lack of experimental evidence supporting this hypothesis. Thymus quinquecostatus CELAK (TQC) extract is a plant from China belonging to the thymus species,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Although the increase in mitochondrial mass is believed to have contributed to the improvement in mitochondrial function against oxidative stress caused by the inflammatory response ( Mills and O’Neill 2016 ; Skuratovskaia et al ., 2020 ), further studies on related mechanisms, including energy metabolism are needed. Nevertheless, our results are in good agreement with the results of previous studies showing that various natural products or drugs with anti-inflammatory effects improved mitochondrial function in LPS-activated macrophages ( Afrin et al ., 2018 ; Hong et al ., 2020 ; Yu et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the increase in mitochondrial mass is believed to have contributed to the improvement in mitochondrial function against oxidative stress caused by the inflammatory response ( Mills and O’Neill 2016 ; Skuratovskaia et al ., 2020 ), further studies on related mechanisms, including energy metabolism are needed. Nevertheless, our results are in good agreement with the results of previous studies showing that various natural products or drugs with anti-inflammatory effects improved mitochondrial function in LPS-activated macrophages ( Afrin et al ., 2018 ; Hong et al ., 2020 ; Yu et al ., 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…For Nrf-2 present in the cytoplasm to act as a transcription factor, it must be liberated from Kelch-like ECH-associated protein 1, a negative regulator of Nrf2, and phosphorylated before translocation to the nucleus ( Loboda et al ., 2016 ; Saha et al ., 2020 ). Interestingly, the improvement in mitochondrial biogenesis by the activation of HO-1 was found to be essential for blocking inflammatory and oxidative reactions by LPS in RAW 264.7 macrophages ( Shi et al ., 2019 ; Hong et al ., 2020 ). In this study, ALA increased LPS-induced HO-1 protein levels, and the degree of phosphorylation of Nrf-2 was also markedly increased in cells co-treated with ALA and LPS, indicating that the activity of Nrf-2 as a transcription factor was improved.…”
Section: Discussionmentioning
confidence: 99%
“…At present, T. quinquecostatus is widely used to treat stroke, cold, dyspepsia, toothache, acute gastroenteritis, hypertension, chronic eczema and other diseases as folk medicines and was used alone or in combination with other herbal medicines for cancer treatment [15,16] . T. quinquecostatus has antioxidative effects that can mediate the inflammatory response and prevent cell damage through its antioxidant activities [17] . Hyun evaluated the antioxidant, antimicrobial, and antidiabetic activities of methanol extract of T. quinquecostatus [18] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, we examined whether IBC enhances mitochondrial biogenesis-related genes (based on mRNA levels) using real-time PCR ( Figure 6 C–G). Previous studies have reported that heme oxygenase-1 ( HO-1 ) is an antioxidant enzyme that is an important regulator of angiogenesis, mitochondria biogenesis, and neurogenesis by increasing the protein expression of NRF-1 , PGC1 , and TFAM [ 25 ]. The expression levels of mitochondrial biogenesis-related genes, including HO-1 , PGC1α , and TFAM , were detected with qRT-PCR analysis.…”
Section: Resultsmentioning
confidence: 99%